The foraging ecology of two sympatric fur seal species, Arctocephalus gazella and Arctocephalus tropicalis, at Macquarie Island during the austral summer - Robinson, S; Goldsworthy, SD; van den Hoff, J; Mark Hindell (2002)
Antarctic Arctocephalus gazella and subantarctic Arctocephalus tropicalis fur seals breed sympatrically at Macquarie Island. The two species have different lactation strategies, the former rearing its pup in 4 months and the latter taking 10 months. The diet and at-sea foraging behaviour of these sympatric species was compared during the austral summer period when their pup rearing period overlapped. The prey of the two fur seal species was very similar, with fish dominating the diet. The myctophid, Electrona subaspera, was the main prey item (93.9%) in all months of the study. There were no major differences in the diving behaviour between species. Both species foraged north of the island parallel to the Macquarie Ridge. Foraging activity was concentrated at two sites: (i) within 30 km north of the island; and (ii) at 60 km north. Most locations for overnight foraging trips were within 10 km of the colonies. The different lactation strategies of A. gazella and A. tropicalis allowed for flexibility in foraging behaviour. At Macquarie Island, the local marine environmental conditions have resulted in similar foraging behaviour for both species.